Los juegos educativos y el aprendizaje en la matemática en niños de la Institución Educación Inicial N°847 Nuestra Señora de la Purísima, Punchana 2023 - Dahua Arimuya, Jazmin (2024)
This quantitative, cross-sectional study investigated whether educational games affect mathematics learning, in a sample of 99 children from I.E.I. N°847 Nuestra Señora de la Purísima Punchana 2023, where the findings show that educational games do not improve mathematics, algebra, geometry or spatial awareness. The evaluation coefficients, ranging from 0.025 to 0.106, indicate a minimal connection between the factors. Furthermore, the high significance level (between 0.298 and 0.803) suggests that Ha cannot be rejected in any case, indicating that there is insufficient statistical evidence to support a significant relationship between educational games and skill acquisition. This could be due to several factors, such as ineffective educational games or factors not considered in the analysis.